Job Stress, Organizational Support, And Turnover Intention Among Generation Z Employees In Digital Startups: Evidence From Makassar - Nur Andini Sudirman (Daengku: Journal of Humanities and Social Sciences Innovation, 2025)
AbstractPurpose: This study examines how Job Stress (X1) and Perceived Organizational Support (POS) (X2) influence Turnover Intention (Y) among Generation Z employees in digital startups in Makassar, Indonesia. Design/methodology/approach: Using a cross-sectional quantitative design, data were collected through a structured Likert-scale questionnaire from Gen Z employees (minimum tenure: six months) working in Makassar-based digital startups. Measurement quality was assessed via item validity and Cronbach’s alpha reliability tests, followed by regression assumption checks (normality, multicollinearity, heteroscedasticity, and linearity). Hypotheses were tested using multiple linear regression. Findings: Job stress has a positive and significant effect on turnover intention, indicating that rising work pressure in fast-paced startup settings (deadline intensity, shifting priorities, and always-on digital demands) increases employees’ propensity to consider leaving. POS has a negative and significant effect on turnover intention, suggesting that perceived appreciation, supervisor responsiveness, and access to resources reduce quitting intentions. Jointly, X1 and X2 explain a substantial portion of variance in turnover intention, implying that support can buffer stress but cannot fully offset chronic overload. Originality/value: This study extends turnover intention evidence to Makassar’s digital startup ecosystem and clarifies the dual levers of stress management and organizational support for Gen Z retention. It offers context-specific insights for emerging Indonesian tech hubs where HR practices are maturing and Gen Z mobility and wellbeing expectations are especially salient. Practical implications: Startups should strengthen workload governance, role clarity, healthy communication boundaries, structured onboarding for fit, and visible support practices (coaching, recognition, fair workload allocation, and timely resources) to reduce quitting intentions. Keywords: Job Stress, Perceived Organizational Support, Turnover Intention, Generation Z, Digital Startups.